Mengurai Nilai Kepemimpinan Gajah Mada dalam Perspektif Pendidikan Ki Hadjar Dewantara - Endhi Hermina Ayu (EKONOMI DAN BISNIS DIGITAL, 2025)
This study aims to examine the relationship between Gajah Mada's leadership values and the educational principles developed by Ki Hadjar Dewantara. The study was conducted using a qualitative approach through interpretive and comparative literature review of historical sources, documents of prominent figures' thoughts, and relevant scientific literature. The results of the analysis show that there are three main values in Gajah Mada's leadership, namely exemplary leadership, collective empowerment, and strategic leadership. These three values are closely related to the principles of Ing ngarsa sung tulada, Ing madya mangun karsa, and Tut wuri handayani, which form the basis of Ki Hadjar Dewantara's educational philosophy. Gajah Mada's exemplary leadership is reflected in his commitment to the Sumpah Palapa oath, in line with the principle of the teacher as a role model. His ability to mobilize the people's strength reflects the importance of building collective spirit from within society, as advocated in the principle of Ing madya. Meanwhile, his effective yet non-dominant leadership strategy aligns with the principle of Tut wuri handayani, which involves providing support from behind to enable learners to develop independently.This finding underscores that historical leadership values can serve as an inspirational source in shaping character education in the modern era. The integration of these values into the education system is believed to strengthen students' exemplary behavior, social responsibility, and independence in facing the challenges of the 21st century